USO DAS GEOTECNOLOGIAS NA ANÁLISE DA FRAGILIDADE AMBIENTAL DA SUB-BACIA DO CÓRREGO DO SÍTIO, BACIA DO RIO TAQUARI, COXIM, MS - SILVA, Érica Martins; ROCHA, Rodrigo; GÜNTZEL, Adriana Maria; OLIVEIRA, Vincler Fernandes Ribeiro (ANAIS DO ENIC, 2020)
-